2021
DOI: 10.15587/1729-4061.2021.238588
|View full text |Cite
|
Sign up to set email alerts
|

Development in mechanical and fatigue properties of AA6061/AL2O3 nanocomposites under stirring temperature (ST)

Abstract: Aluminum is expected to remain the core material for many critical applications such as aircraft and automobiles. This is due to the high resistance to different environmental conditions, desired and manageable mechanical properties, as well as high fatigue resistance. Aluminum nanocomposites such as AA6061/Al2O3 can be made in many ways using a liquid metallurgy method. The main challenges for this method in the production of nanocomposites are the difficulties of achieving a uniform distribution of reinforci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The effect of stirring temperature (ST) on the mechanical and fatigue properties of AA6061/AL 2 O 3 nanocomposites was investigated by the paper [4]. They fabricated the composites using stir casting and conducted mechanical tests.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of stirring temperature (ST) on the mechanical and fatigue properties of AA6061/AL 2 O 3 nanocomposites was investigated by the paper [4]. They fabricated the composites using stir casting and conducted mechanical tests.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Comparison between 17 lowered by 43.963 % at stress level of 540 MPa [11]. Fatigue life experimental results showed that an increase of 17.4 % when addition 9 wt % of Al 2 O 3 to AA6061 compared to matrix fatigue results [4]. The following factors may contribute to improve the fatigue life and strength [10,12]:…”
Section: Test Descriptionmentioning
confidence: 99%